The Influence of Employee Work Discipline in Pagar Merbau I Office on The Quality of Service to the Community in Pagar Merbau I Village - Vicky Amalia Zulmi; Martua Sitorus (Journal of Economics and Business (JECOMBI), 2021)
Quantitative research is a process of finding knowledge using data in the form of numbers as a tool to analyze information about what you want to know. This study aims to determine how the influence of the work discipline of the Pagar Merbau I village office employees on the quality of service to the community in the village of Pagar Merbau I. This research is a descriptive study that relies on a questionnaire distributed to local residents who experience daily administrative services from employees. Pagar Merbau I Village Office, Pagar Merbau District. In processing the data, this research uses SPSS software to simplify calculations in order to obtain accurate and precise calculation results. This research is a research that does a simple regression test because there is only one independent variable and one dependent variable. This study took a sample of 100 local residents and were given a questionnaire of 10 statements. The results of this study reveal that there is a significant and positive influence of work discipline variables on service quality variables. The percentage of influence is 52%. This means that with the existing instruments, work discipline variables can explain the level or quality of public services that occur at the Pagar Merbau I village office, while 48% of the effect is generated by other factors.